Hub companies shaping the future: the ethicality and corporate social responsibility of platform economy giants - Härkönen H; Naskali J; Kimppa K (United States, 2022)
Hub companies (e.g. Amazon, Facebook, Apple, Twitter and Google) rule the internet. They are de facto monopolies in their area of operations. They shape the future in which we live. And, it seems there is nothing we can do about that, as traditional economies of extreme scale – in which eventually the size of a corporation starts to be a hindrance, rather than an advantage – do not apply to them. On the contrary, they keep growing and growing and thus gaining stronger and stronger strangle hold over their respective areas of commerce and influence. This leads to unethical results, where the corporations spin out of any control, national or international. In this paper we give reasons to this phenomenon and lament the future of the internet – unless something drastic is done to change this.
Proceedings of the 2nd ACM SIGSOFT International Workshop on Software-Intensive Business: Start-ups, Platforms, and Ecosystems